Spatiotemporal variability of oxygen concentration in coral reefs of Gorgona Island (Eastern Tropical Pacific) and its effect on the coral Pocillopora capitata - Ana Lucia Castrillón-Cifuentes; Fernando A. Zapata; Alan Giraldo; Christian Wild (PeerJ, 2023)
Dissolved oxygen concentration (DO) is one of the main factors limiting benthic species distribution. Due to ocean warming and eutrophication, the ocean is deoxygenating. In the Eastern Tropical Pacific (ETP), deep waters with low DO (<1 mg L−1) may reach coral reefs, because upwelling will likely intensify due to climate change. To understand oxygen variability and its effects on corals, we characterize the Spatio-temporal changes of DO in coral reefs of Gorgona Island and calculate the critical oxygen tension (Pcrit) to identify the DO concentration that could represent a hypoxic condition for Pocillopora capitata, one of the main reef-building species in the ETP. The mean (±SD) DO concentration in the coral reefs of Gorgona Island was 4.6 ± 0.89 mg L−1. Low DO conditions were due to upwelling, but hypoxia (<3.71 mg L−1, defined as a DO value 1 SD lower than the Mean) down to 3.0 mg O2 L−1 sporadically occurred at 10 m depth. The Pcrit of P. capitata was 3.7 mg L−1 and lies close to the hypoxic condition recorded on coral reefs during the upwelling season at 10 m depth. At Gorgona Island oxygen conditions lower than 2.3 mg L−1 occur at >20 m depth and coincide with the deepest bathymetric distribution of scattered colonies of Pocillopora. Because DO concentrations in coral reefs of Gorgona Island were comparably low to other coral reefs in the Eastern Tropical Pacific, and the hypoxic threshold of P. capitata was close to the minimum DO record on reefs, hypoxic events could represent a threat if conditions that promote eutrophication (and consequently hypoxia) increase.